1998
DOI: 10.1161/01.cir.98.4.346
|View full text |Cite
|
Sign up to set email alerts
|

Activation of gp130 Transduces Hypertrophic Signals via STAT3 in Cardiac Myocytes

Abstract: Background-gp130, a signal transducer of the IL-6 -related cytokines, is expressed ubiquitously, including in the heart.The activation of gp130 in cardiac myocytes was reported to induce myocardial hypertrophy. The downstream side of gp130 consists of two distinct pathways in cardiac myocytes, one a Janus kinase/signal transducer and activator of transcription (JAK/STAT) pathway, the other a mitogen-activated protein kinase (MAPK) pathway. In the present study, we examined whether the JAK/STAT pathway, especia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
153
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 215 publications
(159 citation statements)
references
References 44 publications
(39 reference statements)
4
153
0
Order By: Relevance
“…The construction of recombinant adenovirus/CMVdnStat3 Y705F (rAd/dnStat3) is described previously (Kunisada et al, 1998). DnStat3 was generated from Stat3 by changing the Tyr at position 705 into phenylalanine.…”
Section: Transduction Of Dominant-negative Stat3 Y705f In Cancer Cellsmentioning
confidence: 99%
“…The construction of recombinant adenovirus/CMVdnStat3 Y705F (rAd/dnStat3) is described previously (Kunisada et al, 1998). DnStat3 was generated from Stat3 by changing the Tyr at position 705 into phenylalanine.…”
Section: Transduction Of Dominant-negative Stat3 Y705f In Cancer Cellsmentioning
confidence: 99%
“…Further study showed that CT-1 caused both enhanced survival and hypertrophy of differentiated cardiac muscle cells and inhibited cardiac myocyte apoptosis after serum deprivation or cytokine stimulation (25,30,36,37,40). CT-1, acting through the gp130 receptor common to the IL-6 family, has been reported to be critical in the induction of hypertrophy in response to biomechanical overload and is overexpressed in cardiomyopathy, as part of a panel of "fetal" genes induced in response to damage (14,28).We have demonstrated that CT-1 is detected in abundance in freshly isolated and minced normal adult human lung and is expressed in both fetal and adult human primary cultured bronchial smooth muscle cells (HBSMC), predominantly in synthetic phenotypes. CT-1 induces a significant increase in HBSMC size, as judged by protein-to-DNA ratio and flow cytometry, and reduces the apoptosis induced both by serum deprivation and by Fas antibody/TNF-␣ treatment in HBSMC (38).…”
mentioning
confidence: 99%
“…Further study showed that CT-1 caused both enhanced survival and hypertrophy of differentiated cardiac muscle cells and inhibited cardiac myocyte apoptosis after serum deprivation or cytokine stimulation (25,30,36,37,40). CT-1, acting through the gp130 receptor common to the IL-6 family, has been reported to be critical in the induction of hypertrophy in response to biomechanical overload and is overexpressed in cardiomyopathy, as part of a panel of "fetal" genes induced in response to damage (14,28).…”
mentioning
confidence: 99%
“…These cytokines prevent apoptosis and stimulate cardiac hypertrophy in a manner essentially indistinguishable from the actions of CT-1. All three cytokines stimulate myocyte hypertrophy through activation of the Jak-STAT (Signal Transducers and Activators of Transcription) pathway, and prevent apoptosis through activation of ERK1/2 (Extracellular signal Regulated protein Kinases 1 & 2) and the phosphatidylinositol 3-OH kinase (PI3 kinase)/ Akt pathways [7][8][9][40][41][42][43][44]. LIF is elevated to a greater degree after infarct in mice lacking IL-6 compared to wild type mice [42], and we expected that one or both of these cytokines would be elevated to a greater extent after ischemia-reperfusion in CT-1 −/− mice than in control mice.…”
Section: Discussionmentioning
confidence: 99%